59‐1: Invited Paper: A Full‐color Micro‐light‐emitting‐diode Display by a Lithographic‐fabricated Photoresist Mold. Issue 1 (30th May 2018) - Lin, Chih-Hao; Lee, Chun-Fu; Verma, Akta; Lin, Huang-Yu; Lin, Chien-Chung; Sher, Chin-Wei; Kuo, Hao-Chung
Abstract : In this paper, we will review our lab's result on using photoresist as the masking material for micro‐LED arrays. The colloidal quantum dots (QDs) are used as photon conversion layer and the Aerosol Jet ® technology was applied for dispensing the QDs. A full‐color array can be demonstrated and the isolation between pixels can be improved. The output light intensity can also be improved via the inclusion of a ultra‐violet band distributed Bragg reflector (DBR).